Fenomena Game Online Mobile Legends Di Jakarta Barat (Studi Fenomenologi Pada Kalangan Pelajar SMA Yadika2 Tegal Alur) - Ardo, Firman Daniel; Nursanti, Siti; Oxcygentry, Oky (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This research aims to explore the phenomenon of playing Mobile Legends among students, focusing on five informants from Yadika 2 High School students in Tegal Alur, West Jakarta. The researcher delves deeper into the motives, meanings, and experiences students undergo while playing the online game Mobile Legends. The study employs a phenomenological method, with data collection conducted through interviews, observations, and supported by literature reviews. The results of the research on the phenomenon of playing Mobile Legends among students show that there are two types of motives. The causal motives are having fun, making friends, and filling spare time, while the goal-oriented motives are self-motivation to become competitive, aiming to become professional players, and sharpening mental skills. The meanings that arise from the students include learning self-control, learning communication, improving abilities, and engaging in social interactions. The students experiences during gameplay include experiences in communication with other players and participation in competitions.